Assessment of soil fertility status in cotton-based cropping systems in Cote d’Ivoire - Koné, Ismail; Kouadio, Konan-Kan Hippolyte; Kouadio, Emmanuel N’Goran; Agyare, Wilson Agyei; Owusu-Prempeh, Nat; Amponsah, William; Gaiser, Thomas (Frontiers in Soil Science, 2022)
Cotton is the main cash crop in northern Côte d’Ivoire, where intensive cultivation along with low external inputs has led to a decline in crop yields due to soil degradation. The present study aims to assess the evolution of soil fertility during the 2013 and 2021 periods in the cotton basin area of Côte d’Ivoire. More specifically, the study (i) identified the limiting physico-chemical parameters of soil fertility, and (ii) analysed the state of evolution of soil fertility in 2013 and 2021 in the cotton basin of Côte d’Ivoire. For this purpose, a total of 64 soil samples were taken in 2013 and in 2021 on the same cotton plots on the 0-20 cm horizon. Chemical analyses of the soil samples in the laboratory were carried out on the following parameters: particle size distribution, pH water, total nitrogen (NT), Potassium (K+), Calcium (Ca2+), Magnesium (Mg2+), Sodium (Na+) and Cation exchange capacity (CEC). The results of the soil analyses showed that the sandy-clay textured topsoils dominate the whole study area in both years. This leads to a low retention capacity of exchangeable bases. Determination of the soil pH showed that the pH varies from slightly acidic to neutral (6.5<pH<7). The most limiting chemical properties are Cation exchange capacity (CEC) and the sum of the exchangeable bases (SEB) in the department of Korogho, Boundiali, and Ferkessedougou and the most limiting chemical properties in the department of Mankono are CEC. However, during the period from 2013 to 2021 the content of exchangeable cations (Ca2+, Mg2+ and K+) and the base saturation (BS) increased significantly in all the departments, more precisely in the department of Mankono. Although we observed a slight increase in the chemical properties of the soils in 2021 compared to 2013, the values were still below the minimum required threshold. This result implies that the soils have poor physico-chemical properties and consequently a low level of fertility, which compromises the sustainability of the cotton production system. The application of organic and mineral amendments is therefore essential to increase the nutrient content of these soils.